Ženstvena-da, svakako! Feministkinja-nikako! - Potkonjak, Sanja (2004)
This paper is a "feminist" portrait of Croatian educationalist, ethnographer, and writer Jelica Belović Bernadzikowska (1870-1946).Her importance arises from less known work on "feminine question." The paper aims at analysing popular writings of JBB, pointing to the paradox of maternal feminism discussed in her work.